Reimplantation of an Anomalous Coronary Artery Arising from the Pulmonary Artery. (25th March 2009) - Quarti, Andrea; D'Alfonso, Alessandro; Colaneri, Massimo; Baldinelli, Alessandra; Bettuzzi, Maria Grazia; Pozzi, Marco
Abstract : A case of anomalous origin of the left coronary artery from the pulmonary artery in a patient with the origin of the coronary opposite to the aorta is reported. Between many surgical options we conclude to reestablish a double coronary system reconnecting the coronary through a conduit created with a pulmonary wall baffle and an autologous pericardial patch.